Learning Through Experience: Uncovering the Needs of Nursing Students to Enhance Group Dynamics. - Dionne Merlin, Marjolaine; Boudreau, Julie Émelie; Jessica, Aucoin; Camylle, LeBlanc (International Journal of Caring Sciences)
Background: Clinical placements are key to nursing education, offering experiential learning in the Clinical Learning Environment (CLE). Students' experiences are shaped by their context and background. In the group practicum model, a unique group dynamic naturally develops and significantly shapes the learning experience. Various CLE factors can influence how these group dynamics unfold. Understanding students' needs is essential to fostering effective group dynamics and ensuring meaningful, supportive learning experiences. Aims: Exploring and describing the needs of nursing students to promote the development of effective group dynamics within the context of experiential learning. Methodology: A qualitative study using interpretive description was conducted with undergraduate nursing students at a French-language university in Canada. Maximum variation purposive sampling ensured diverse clinical experiences. Data were collected through semi-structured interviews and focus groups, then thematically analyzed using Miles, Huberman & Saldaña (2019) iterative framework. Analysis was supported by Dedoose software and conducted collaboratively to enhance credibility. Results: Six themes define nursing students' needs during clinical placements: fostering a sense of belonging, experiencing structured clinical supervision, mobilizing personal resources to navigate the emotional experience of clinical placement, evolving within a clinical placement structure conducive to learning, building connections with nursing staff and developing critical thinking. Conclusions: Understanding the needs of nursing students is essential for promoting effective group dynamics and building a supportive CLE, thereby enriching their learning experiences and fostering professional development. These findings underscore the importance of intentional collaboration between academic and clinical partners to create psychologically safe, well-structured learning settings. Addressing students' interpersonal and contextual needs not only supports their academic and clinical success but also contributes to the formation of compassionate and competent future nurses.